2019
DOI: 10.1111/jfpp.14002
|View full text |Cite
|
Sign up to set email alerts
|

Use of a waste product from the pressing of chia seed oil in wheat and gluten‐free bread processing

Abstract: The aim of the paper was to evaluate the effect of a waste product from the pressing of chia seed oil on wheat and gluten‐free bread baking. The bread quality (pH, volume, color, texture, and sensory properties), polyphenol content, and antioxidant activity were determined. Chia seeds and chia seed waste, which have fat contents of 6 and 15%, respectively, were added at a level of 5%. The addition of the chia waste and seeds to the wheat bread was found to increase the bread volume with no deterioration in its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…The same results showed that the bread with 2.5% chia flour had specific volume similar to the ***control. Zdybel, Różyło, and Sagan (2019) similarly noticed that addition of 5% of chia flour significantly reduced volume of 100g of gluten-free bread. Moreover, sweet basil seeds in the amount of 1.0 and 1.5% that were used as an ingredient (Rezapour et al, 2016) reduced the volume of baguettes.…”
Section: Resultsmentioning
confidence: 83%
“…The same results showed that the bread with 2.5% chia flour had specific volume similar to the ***control. Zdybel, Różyło, and Sagan (2019) similarly noticed that addition of 5% of chia flour significantly reduced volume of 100g of gluten-free bread. Moreover, sweet basil seeds in the amount of 1.0 and 1.5% that were used as an ingredient (Rezapour et al, 2016) reduced the volume of baguettes.…”
Section: Resultsmentioning
confidence: 83%
“…In our study the fiber content of the protein-enriched bread was equal to 13.7%, there were no significant differences in the fiber, and fat content between the control bread, and the 10% PPP-based bread. The resulting low-carbohydrates, and high protein bread have a low-calorific value, compared to other breads whose calorific value in various publications were at a level of more than 200 kcal/100g 20 , 30 . Conventional wheat bread presents low protein, high carbohydrate, and small amounts of dietary fibre 6 .…”
Section: Resultsmentioning
confidence: 87%
“…Buckwheat, and flaxseed flour were selected for the bread recipe based on the available literature, and chemical analysis as raw materials with a low carbohydrate content. For example, white wheat flour usually contains more than 70% carbohydrates 30 , and rice flour at most 80% 22 , 30 , while corn flour has usually even more than 80% carbohydrates 30 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of ROF is also economically important and is in line with current global trends. Waste materials are increasingly used in food processing, and therefore the utilisation of by-product is an interesting solution in bread production (Zdybel et al 2018). The obtained results showed that there is a possibility to use by-product and non-bread cereal as potential raw materials for designing and creating novel food.…”
Section: Discussionmentioning
confidence: 99%